Proposed methodology to assess Islamicisation of human knowledge (IoHK) in the built environment education: a case study of Kulliyyah of Architecture & Environmental Design (KAED), International Islamic University Malaysia (IIUM) - Ahmad Sarkawi, Azila; Abdul Rashid, Khairuddin; Aripin, Srazali (2013)
Islamicisation of knowledge touches every aspects of human knowledge including the built environment. It becomes a critical agenda nowadays due to ‘dualism educational system’ that we practiced. Therefore, some integrations between secular and Islamic form of knowledge is hoped to happen in educational system without compromising the sacredness of Islam. Being an Islamic University, the agenda was already in place since the establishment of IIUM in 1983. It is timely for assessing the achievement of this agenda in particular the courses offered. Hence, the paper attempts to present the methodology towards assessing the Islamicisation of human knowledge in the built environment educational system, a case study of Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia (IIUM). Having said that, all courses offered in academic session 2010/2011 are being surveyed looking at its level and type of Islamic inputs based on fifteen modes of Islamicisation agenda practiced in IIUM. A study delved into the lecturers’ perspectives of Islamic input in the course outline for fourteen weeks of teaching. A customized questionnaire form is emailed to all academic staff for them to tick the type of Islamicisation mode applied in their teaching courses weekly. At the end, the form is self calculated for level of Islamic input ranging from 0-20 indicates poor; 21-40 indicates low; 41-60 indicates average; 61-80 indicates good; and 81-100 indicates excellent. This survey also is able to collate types/modes of Islamicisation took place in KAED. For these two objectives of the survey, the paper is only presenting the second objective’s outcome that is types/modes of Islamicisation took place in KAED’s courses offered. This proposed method of assessing Islamic input in courses offered is hoped to be extended to other Kulliyyahs in IIUM for the Islamicisation agenda.